2005
DOI: 10.1002/dev.20091
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, loss, and complicated grief

Abstract: Bereavement is a highly disruptive experience that is usually followed by a painful but time-limited period of acute grief. An unfortunate minority of individuals experience prolonged and impairing complicated grief, an identifiable syndrome that differs from usual grief, major depression, and other DSM IV diagnostic entities. Underlying processes guiding symptoms are not well understood for either usual or complicated grief. We propose a provisional model of bereavement, guided by Myron Hofer's question "What… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
260
2
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 322 publications
(295 citation statements)
references
References 93 publications
16
260
2
11
Order By: Relevance
“…Eighty (63%) met criteria for current Major Depression. Severity of depression and anxiety were assessed using the rater-administered 17-item Hamilton Depression (HRSD) [18] and Hamilton Anxiety (SIGH-A) [43,46] Rating Scales. Complicated grief severity was assessed using the Inventory of Complicated Grief (ICG) [39].…”
Section: Grief-related Avoidance Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…Eighty (63%) met criteria for current Major Depression. Severity of depression and anxiety were assessed using the rater-administered 17-item Hamilton Depression (HRSD) [18] and Hamilton Anxiety (SIGH-A) [43,46] Rating Scales. Complicated grief severity was assessed using the Inventory of Complicated Grief (ICG) [39].…”
Section: Grief-related Avoidance Behaviormentioning
confidence: 99%
“…We believe the effectiveness of this complicated grief treatment provides indirect support for the validity of the underlying model, though clearly there is a need for studies directly testing specific components of this model. Distribution of Scores on the Grief-related Avoidance Questionnaire Complicated grief pathway elaborated from Shear and Shair [46] Table 2 Complicated grief treatment goals and strategies…”
Section: Bereavement As a Traumatic Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…homicide/accident/disaster-related loss) has been associated with higher PG, PTS, and depression levels compared with non-violent loss (Boelen, de Keijser, & Smid, 2015; Kaltman & Bonanno, 2003; Kloep, Lancaster, & Rodriguez, 2014). Empirical work, drawing from cognitive-behavioural theories of grief (Boelen, van den Hout, & van den Bout, 2006a; Maccallum & Bryant, 2013; Shear & Shair, 2005), has shown that negative cognitions and avoidance behaviour may explain the debilitating impact of traumatic loss (Boelen et al, 2015; Mancini, Prati, & Black, 2011). According to Boelen et al’s (2006a) cognitive-behavioural model, three processes play a crucial role in the onset and maintenance of post-loss psychopathology: insufficient integration of the loss into the autobiographical knowledge base, negative cognitions, and avoidance behaviour.…”
mentioning
confidence: 99%